Terapi Mindfulness terhadap Kesehatan Mental Remaja - Annisa Mazda Firdaus; Dian R. Sawitri; Meidiana Dwidiyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the effectiveness of mindfulness interventions on mental health conditions in adolescents. The method used is a systematic literature review with seven national and international research articles reviewed utilizing the search engines PubMed, Scopus, Science Direct, and Google Scholar within the last six years. The research results from the identification of 7 research articles found significant effects of mindfulness interventions on adolescent mental health conditions, such as increasing the ability to regulate emotions, resilience, and reducing stress, depression, and anxiety. The conclusion of this literature review strengthens the effectiveness of mindfulness in improving adolescent mental health in a more positive direction. Keywords: Mental Health, Mindfulness, Adolescents